Therapeutic benefits of glycerol in dry eye disease - Victoria Ronderos; Wendy B. Bollag; Wendy B. Bollag; Wendy B. Bollag (Frontiers in Medicine)
Dry eye disease (DED) is one of the most commonly diagnosed eye disorders, with a prevalence ranging from 5 to 50%, depending on the geographic location. DED is a multifactorial disorder of the tears and ocular surface, which results in symptoms of discomfort, visual disturbance, and tear film instability with potential damage to the ocular surface. It is also accompanied by increased osmolarity of the tear film and inflammation of the surface of the eye. Multiple therapeutic agents have been used to treat DED, with glycerol emerging as a promising component of ophthalmic preparations, due to its humectant, lubricant, demulcent, and osmoprotective properties. This review aims to evaluate the current evidence concerning the therapeutic benefits of glycerol in managing DED, focusing on its possible mechanisms of action, clinical efficacy, and potential advantages over other treatments.